MASHUP COMPILATION AND MASHUP OF SCREENING AS BRAINSTORM OF CLASSIC NOVELS / MASHUP-КОМПИЛЯЦИИ И MASHUP-ЭКРАНИЗАЦИИ КАК МОЗГОВОЙ ШТУРМ КЛАССИЧЕСКИХ РОМАНОВ - SARASKINA L.I. / САРАСКИНА Л.И. (Наука телевидения)
The article considers the problem of adaptation of literary works as part of contemporary screen culture. The author argues that literary centricity of culture is still alive, and literature breaks through the barriers to media, penetrates in blogs, spams in social networks. By the example of works of zombie literature and zombie movies, mashup adaptations of cyberpunk and steampunk, the author shows that this connection gives nothing to the understanding of the literary foundations, classic books, available not for entertainment.